The Effect of Commitment, Motivation, and Leadership on Heads and Teachers Performance in the Junior High School in Rimba Melintang - Yarmanelis; Sarli Rahman; Achmad Tavip Junaedi; Mujtaba M. Momin (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This research was conducted to know and analyze the influence of commitment, motivation, and leadership on the satisfaction and performance of teachers in the SMP Rimba Melintang Sub-district. This study was chosen because of the phenomenon and problems related to the satisfaction and performance of elementary school teachers in the Rimba Melintang sub-district. This is of course related to many factors, but the authors have a conjecture that factors of commitment, motivation, and good leadership will affect and improve teacher satisfaction and performance. The method used in data collection and this research is a questionnaire. The results of this study are: (1) There is a significant and positive influence between commitment to satisfaction. (2) There is a significant and positive influence between motivation to satisfaction. (3) There is no significant influence between leadership and satisfaction. (4) There is no significant influence between commitment to performance. (5) There is no significant influence between motivation on performance. (6) There is no significant influence between leadership on performance. (7) There is no significant influence between satisfaction with performance.